Simultaneous detection of circulating and disseminated tumor cells in primary breast cancer patients following neoadjuvant chemotherapy - Walter, Vincent P.; Wallwiener, Markus (Archives of gynecology and obstetrics, 2018)
PURPOSE: Pathological complete response (pCR) is a common endpoint in neoadjuvant chemotherapy (NACT) of primary breast cancer patients (PBC), but does not address the systemic prevalence of minimal residual disease. In this study, we compared pCR with the detection of circulating (CTC) and disseminated tumor cells (DTC) following NACT, as well as their impact on survival. - METHODS: Patients with PBC receiving NACT and consecutive surgery were eligible for this study. CTCs were detected using the CellSearch® system and DTCs were determined using immunocytochemistry (cytokeratin staining with the A45-B/B3 antibody). pCR was defined as ypT0/ypTis and ypN0. - RESULTS: 58 patients were included in the analysis with a median follow-up of 30 months. Of these, 5 (9%) presented with CTCs and 36 (62%) with DTCs. 16 patients (28%) achieved a pCR. No significant correlation between CTCs, DTCs and pCR and no statistically significant impact on disease free (DFS) or overall survival (OS) was apparent. - CONCLUSIONS: Both CTCs and DTCs are detectable after NACT. As we could not show a significant relationship between CTC detection, DTC detection and pCR, all three methods may provide independent information regarding treatment response. Since we were unable to show a significant impact on survival, larger prospective studies that include CTCs and DTCs are needed. These trials should include the molecular characterization of primary tumor tissue, CTCs and DTCs to determine whether these cells are independent subpopulations of malignant cell clones.
Gesehen am 29.04.2019